Web-based Mobile Service for Pollution Monitoring Systems - Mitreski, Kosta; Stevkovski, S (institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2003)
Mobile Web Services bridge the gap between the mobile world and offer the ability to deliver an unlimited range of mobile-value added services to subscribers. The paper presents the usability of wireless network services in Ecology. We’ve developed a mobile service that allows for online inserting and retrieving data from an Information System database that serves as a pollution monitoring system. The service works on a previously developed Information System for pollution monitoring of Lake Ohrid. The Application is created in a .NET environment, which gives us the possibility to “develop once” and serve any kind of mobile device.
Keywords: mobile, service, monitoring, wireless network, .NET, Information system